La escuela francesa de didáctica de las matemáticas y la construcción de una nueva disciplina científica - Ruiz, Angel (2008)
A brief review about the French Didactique des Mathématiques is accomplished, and a theoretical assessment on these ideas is developed. We give an emphasis to the epistemological dimensions.